Research of Modeling and Analysis of Meshing Stiffness of Vehicle Planetary Gear - Zhang Qiang; Wu Zhe; Li Hongwu (Jixie chuandong)
The periodical variation of meshing stiffness of the gear pair is the main internal excitation of the vibration generated by the planetary gear transmission system. It is of great significance to deeply study the meshing stiffness of the gear system for the vibration characteristics of the gear system. The energetic method,the finite element method and the rectangular wave method are used to establish the meshing stiffness model of planetary gears respectively. These three models are used to solve the integrated meshing stiffness of the solar wheel,planetary gear and internal ring gear respectively. Then,the advantages and disadvantages of these three models for calculating mesh stiffness are compared. The results show that the vibration acceleration amplitudes of compound planet gear members under these three kinds of stiffness excitations have a small difference. The amplitude of vibration acceleration calculated by the finite element method is slightly larger than that calculated by the analytical method,and the amplitude of the acceleration calculated by the rectangular wave method is the smallest.